2018
DOI: 10.1177/2168479017725557
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Applications for Pediatric Care: Review and Comparison

Abstract: Medscape, Skyscape, and iGuideline are the most comprehensive mHealth apps for HCPs as quick references for pediatric care. More studies about mHealth apps in pediatric care are warranted to ensure the quality and reliability of mHealth apps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…A long waiting time for a medical consultation has become an important factor affecting outpatient satisfaction [21, 22]. It was necessary to conduct more research on medical health applications in children’s health care centers to ensure the quality and reliability of mobile health applications [23].…”
Section: Discussionmentioning
confidence: 99%
“…A long waiting time for a medical consultation has become an important factor affecting outpatient satisfaction [21, 22]. It was necessary to conduct more research on medical health applications in children’s health care centers to ensure the quality and reliability of mobile health applications [23].…”
Section: Discussionmentioning
confidence: 99%
“…The included mobile apps were assessed based on their basic features and functionalities. The basic features were modified from the outline of developed classification of mHealth apps evaluation criteria proposed by Nouri et al [ 21 ] and in the literature [ 11 , 16 , 22 ]. The included seven basic features were (1) no internet requirement, (2) size of app less than 50 MB, (3) no subscription needed (ie, free), (4) educational content (COVID-19 teaching), (5) export data (sharing of user’s data with other platforms), (6) automated data entry (automatic update of data without user interference), and (7) advisory function.…”
Section: Methodsmentioning
confidence: 99%
“…It is more effective to deliver health-related information through mHealth apps, as information can be exchanged rapidly and updated dynamically [ 10 ]. Mobile apps can potentially prevent the occurrence of a particular disease, as exchanged texts through a mobile app can promote communication, storage of information, and message delivery that drives users to make healthy lifestyle changes [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation in this study included the intended use, reliability, usability and privacy of the apps, but not the technical quality and development or risk management. A study by Morse et al [32] assessed only the presence of different features, such as a dosing calculator, interaction checker or availability of dose recommendations; in this study, too, the technical specifications and risk management features were not assessed. Findings from a review by Boulos et al [33] confirmed the need to develop medical apps and devices in conformity with the EU Medical Devices Directive [17].…”
Section: Action Dmentioning
confidence: 99%